2007
DOI: 10.1111/j.1420-9101.2007.01382.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence of Pleistocene bidirectional faunal exchange between Europe and the Near East: the case of the bicoloured shrew (Crocidura leucodon, Soricidae)

Abstract: We sequenced 1077 bp of the mitochondrial cytochrome b gene and 511 bp of the nuclear Apolipoprotein B gene in bicoloured shrew (Crocidura leucodon, Soricidae) populations ranging from France to Georgia. The aims of the study were to identify the main genetic clades within this species and the influence of Pleistocene climatic variations on the respective clades. The mitochondrial analyses revealed a European clade distributed from France eastwards to north‐western Turkey and a Near East clade distributed from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 52 publications
3
27
1
Order By: Relevance
“…Genetic structure of G. glis.-In contrast to the other studies of European rodents, which reported high levels of genetic divergence (Brunhoff et al 2003;Cosson et al 2005;Deffontaine et al 2005Deffontaine et al , 2009Dubey et al 2007;Fink et al 2004;Searle 2002, 2004;Kotlik et al 2006;Michaux et al 2003Michaux et al , 2005Neumann et al 2005), our results show very low genetic variability in G. glis. The evolutionary trees and haplotype network divide G. glis into 3 wellsupported genetic lineages that have nonoverlapping geographical distributions (with the exception of Sicilian animals occurring in 2 different haplogroups).…”
Section: Discussioncontrasting
confidence: 55%
“…Genetic structure of G. glis.-In contrast to the other studies of European rodents, which reported high levels of genetic divergence (Brunhoff et al 2003;Cosson et al 2005;Deffontaine et al 2005Deffontaine et al , 2009Dubey et al 2007;Fink et al 2004;Searle 2002, 2004;Kotlik et al 2006;Michaux et al 2003Michaux et al , 2005Neumann et al 2005), our results show very low genetic variability in G. glis. The evolutionary trees and haplotype network divide G. glis into 3 wellsupported genetic lineages that have nonoverlapping geographical distributions (with the exception of Sicilian animals occurring in 2 different haplogroups).…”
Section: Discussioncontrasting
confidence: 55%
“…Similarities with phylogeographic patterns of M. arvalis data from several genetic markers (cytb, CR, microsatellites) [33], [34], as well as data from other temperate species [3], [13], [42]–[45] suggest that the distribution of populations between Western and Eastern Europe reflects the evolutionary history of populations rather than genetic marker genealogy. Molecular dating indicates that the population divergence, from the lineage origin to the origin of the Spanish clade of M. arvalis , occurred during the Middle and Late Pleistocene (0.475–0.086 Myr), and thus predated the LGM widely.…”
Section: Discussionmentioning
confidence: 56%
“…The C and E lineages have a shallow regional genetic structure. Low nucleotide diversity (0.53% and 0.62%, respectively), star-like topologies (Figure 2) and analyses of demographic history indicating sudden expansion (Figure 3) provide evidence for a past bottleneck event followed by probable post-LGM population expansion [45][47]. The oldest major W lineage presents a higher level of nucleotide diversity (1.31%) suggestive of relatively large population sizes, and shows a hierarchical phylogeographic structure (NE and SW sublineages) as observed in the field vole [43].…”
Section: Discussionmentioning
confidence: 98%
“…Although based on a small sampling, our data do not support the hypothesis of a refugium located in the Balkan area. This pattern of more stable populations in the Balkans has already been described for the bi-coloured shrew (Crocidura leucodon; Dubey et al, 2007b) and the yellow-necked fieldmouse (Apodemus flavicollis; Michaux et al, 2005). This might be explained by milder climatic conditions prevailing in places farther from the ice sheet.…”
Section: Lebarbenchon Et Almentioning
confidence: 80%